Web-Based Decision Support Information System Design of Lecturer Performance Assessment at the Faculty of Islamic Studies, Islamic University Attahiriyah - Somaida, Muhammad Hasymi; Gunawan, Bambang (Politeknik Negeri Madiun, 2019)
Faculty of Islamic Attahiriyah Islamic University (UNIAT) Jakarta is one of the private universities under the auspices of the Region I Jakarta Coordinator of Islamic Religion (KOPERTAIS), In the process of evaluating the performance of lecturers in the Islamic Faculty of Islamic University of Attahiri, every year. Lecturers who are selected as lecturers by having excellent performance appraisals will later get an award from the Faculty leadership (Dean of the Faculty of Islamic Religion). From this process, it takes a long time to process the calculation of who the lecturer is by assessing his excellent performance and also documents stored in the form of files stored on the archive shelf. One problem solving to find a solution from the system that runs above is by designing a decision support system application for lecturer performance assessment using a web-based Weighted Product (WP) method so that the lecturer performance appraisal can be done in real time and efficiently. Software The application of lecturer performance appraisal decision support can be applied directly as a problem solving solution, carry out maintenance on the application regularly every month so that something or damage occurs so that if a problem occurs it can restore the database again.